Differential synaptic mechanism underlying the neuronal modulation of prefrontal cortex, amygdala, and hippocampus in response to chronic postsurgical pain with or without cognitive deficits in rats - Li, Zhen; He, Zhigang; Li, Zhixiao; Sun, Tianning; Zhang, Wencui; Xiang, Hongbing (Frontiers in Molecular Neuroscience, 2022)
Chronic Postsurgical Pain (CPSP) is well recognized to impair cognition, particularly memory. Mounting evidence suggests anatomic and mechanistic overlap between pain and cognition on several levels. Interestingly, the drugs currently used for treating chronic pain, including opioids, gabapentin, and NMDAR (N-methyl-D-aspartate receptor) antagonists, are also known to impair cognition. So whether pain-related cognitive deficits have different synaptic mechanisms as those underlying pain remains to be elucidated. In this context, the synaptic transmission in the unsusceptible group (cognitively normal pain rats) was isolated from that in the susceptible group (cognitively compromised pain rats). It was revealed that nearly two-thirds of the CPSP rats suffered cognitive impairment. The whole-cell voltage-clamp recordings revealed that the neuronal excitability and synaptic transmission in the prefrontal cortex and amygdala neurons were enhanced in the unsusceptible group, while these parameters remained the same in the susceptible group. Moreover, the neuronal excitability and synaptic transmission in hippocampus neurons demonstrated the opposite trend. Correspondingly, the levels of synaptic transmission-related proteins demonstrated a tendency similar to that of the excitatory and inhibitory synaptic transmission. Furthermore, morphologically, the synapse ultrastructure varied in the postsynaptic density (PSD) between the CPSP rats with and without cognitive deficits. Together, these observations indicated that basal excitatory and inhibitory synaptic transmission changes were strikingly different between the CPSP rats with and without cognitive deficits.